2015
DOI: 10.3390/safety1010016
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration into Younger and Older Pedestrians’ Risky Behaviours at Train Level Crossings

Abstract: Abstract:Background: Younger and older pedestrians are both overrepresented in train-pedestrian injury and fatality collision databases. However, scant research has attempted to determine the factors that influence level crossing behaviours for these high risk groups. Method: Five focus groups were undertaken with a total of 27 younger and 17 older pedestrian level crossing users (N = 44). Due to the lack of research in the area, a focus group methodology was implemented to gain a deeper exploratory understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…Factores cognitivos como la falta de atención, distracción, poco conocimiento, mal juicio, distancia de visión limitada, etc. (Freeman et al, 2013) pueden ser los que llevaran a la aparición de este tipo de errores.…”
Section: Marco Teórico Análisis De La Seguridad En Los Pasos a Nivel ...unclassified
See 2 more Smart Citations
“…Factores cognitivos como la falta de atención, distracción, poco conocimiento, mal juicio, distancia de visión limitada, etc. (Freeman et al, 2013) pueden ser los que llevaran a la aparición de este tipo de errores.…”
Section: Marco Teórico Análisis De La Seguridad En Los Pasos a Nivel ...unclassified
“…En la literatura se citan varios factores que influyen en la tendencia de los usuarios a incumplir las reglas, entre ellos: factores individuales como la edad, el género, la personalidad y las actitudes; factores sociales como normas, cumplimiento y comportamiento de otras personas cercanas; y factores puntuales como el tiempo de espera, el clima, la distracción y el estado de ánimo (Edquist, 2011). Algunas razones más específicas para infringir deliberadamente las reglas de tránsito o de los pasos a nivel incluyen: tener prisa, la conveniencia, la familiaridad, la fatiga o el consumo de alcohol y drogas, entre otros (Freeman et al, 2013).…”
Section: Marco Teórico Análisis De La Seguridad En Los Pasos a Nivel ...unclassified
See 1 more Smart Citation
“…The main task of automatic level crossing systems is to ensure the safety of road users and approaching trains [1][2][3]. They must comply with the requirements of Safety Integrity Level 4 [4] as the consequences of the majority of incidents are usually very severe.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown road user behaviour to be the most prominent factor in collisions between trains and road users at railway level (at-grade) crossings [3,4]. Among the factors influencing non-compliance with railway level crossing (RLX) rules are errors of perception, errors of judgement and deliberate attempts to circumvent safety-oriented countermeasures (including regulatory and engineering measures) [5][6][7]. Within the category of deliberate circumvention, road user frustration and reluctance to wait as directed has been identified as one of the underlying factors in RLX violations [8].…”
Section: Introductionmentioning
confidence: 99%